MIRERC 077/2025: Assessing the Effectiveness of Social Health Authority Maternal Health Services on Maternal Health Care in Nyambene Sub-County Hospital - Maina, Monica Gakii; Dr. Zachary Muriuki; Dr. Mary Amatu (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Social Health Authority is a Kenyan state corporation established under the Social Health Insurance Act of 2023 to manage public health insurance including maternal health services. Despite progress in maternal health services in Kenya and Meru County, significant gaps persist in the utilization of maternal health services. These challenges are compounded by high maternal mortality rates, prevalent obstetric complications, and insufficient facility-specific research and documentation. This study assesses the effectiveness of SHA-funded maternal healthcare services at Nyambene Sub-County Hospital in Igembe South, a leading health facility in Meru County with a high volume of patients seeking maternal health services. It assesses maternal healthcare utilization, maternal morbidity and mortality, and beneficiary satisfaction. A cross-sectional study will involve randomly selected women who have benefited from SHA maternal health services. Data will be collected using pretested, structured questionnaires and a checklist to extract information from the DHIS, with assistance from health record officers. The data will be analyzed using SPSS to generate descriptive and inferential statistics. Ethical clearance will be secured from the Meru University Institutional Research Ethics Committee, NACOSTI and Meru County government, alongside informed consent from participants. The study’s results will offer evidence-based insights to refine maternal health initiatives, guide policy development, and improve service provision in Nyambene Sub County Hospital and comparable areas, supporting Kenya’s pursuit of universal health coverage and Sustainable Development Goal 3. 1.